2019
DOI: 10.1128/aac.00980-19
|View full text |Cite
|
Sign up to set email alerts
|

Early Discontinuation of Ethambutol in Pulmonary Tuberculosis Treatment Based on Results of the GenoType MTBDRplus Assay: a Prospective, Multicenter, Noninferiority Randomized Trial in South Korea

Abstract: No studies have investigated whether the discontinuation of ethambutol (EMB) based on susceptibility to isoniazid and rifampin, as determined by the GenoType MTBDRplus assay, would be appropriate. We aimed to determine the feasibility of discontinuing EMB before the end of the intensive phase of treatment based on the results of the MTBDRplus assay in patients with pulmonary tuberculosis (PTB). This prospective, multicenter noninferiority randomized trial was conducted at 12 referral centers in South Korea in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…To our knowledge, only 1 prospective clinical trial confirmed those results with an 86% sensitivity and 97.8% specificity for isoniazid resistance detection. Indeed, Jo et al [ 13 ] showed that early testing on respiratory smears or positive cultures with Genotype MTBDR plus version 2.0 allowed a reduction in the median duration of ethambutol treatment from 75 to 14 days, with no negative impact on treatment success. Our population was different from this South Korean study given that we only enrolled smear-positive tuberculosis, because our aim was to detect resistance in the very first days after tuberculosis diagnosis to allow us to start an ethambutol-free regimen.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, only 1 prospective clinical trial confirmed those results with an 86% sensitivity and 97.8% specificity for isoniazid resistance detection. Indeed, Jo et al [ 13 ] showed that early testing on respiratory smears or positive cultures with Genotype MTBDR plus version 2.0 allowed a reduction in the median duration of ethambutol treatment from 75 to 14 days, with no negative impact on treatment success. Our population was different from this South Korean study given that we only enrolled smear-positive tuberculosis, because our aim was to detect resistance in the very first days after tuberculosis diagnosis to allow us to start an ethambutol-free regimen.…”
Section: Discussionmentioning
confidence: 99%